Hiện trạng phát triển kinh tế trang trại ở tỉnh Bình Định - Phạm Anh Vũ; Đặng Thị Ngọc Thanh; Trương Thị Thùy Trang; Nguyễn Thị Tường Vy (My University, 2019)
Hiện trạng phát triển kinh tế trang trại ở tỉnh Bình Định
Keywords: Kinh tế trang trại